Action of bioactive compounds in cellular oxidative response. (February 2020) - Pessoa, A.; Miranda, C.F.; Batista, M.; Bosio, M.; Marques, G.; Nunes, F.; Quinta-Ferreira, R.M.; Quinta-Ferreira, M.E.
Abstract: Nowadays there is a growing demand for biodiesel production which can be made, among other resources, from mushroom biomass. It is well established the continuous growth of the population affected with premature aging and numerous diseases in which reactive oxygen species (ROS) are implicated. This fact leads to an increasing consumption of antioxidant rich nutrients, such as mushrooms, which are effectively produced on lignocellulosic biomass substrate. The aim of this study was to investigate, in brain slices, the effect of polysaccharides extracted from the Boletus edulis and Tricholoma equestre mushroom species, in the formation of neuronal ROS, using the fluorescent indicator H2 DCFDA. The polysaccharides compounds from both mushroom species had no effect on ROS signals at 0.1 g/L and 0.5 g/L, but decreased the amplitude of the signal at the concentration of 1.0 g/L. These results are in agreement with the idea that polysaccharides have antioxidant properties. Besides the nutritional value of mushrooms, the biomass residues from their production can be used as raw material for bioethanol and biobutanol production, being the later an even more efficient biofuel than ethanol or methanol.